A Study on the Dynamic Pressure Comfort of Tight Seamless Sportswear (Journal of Fiber Bioengineering and Informatics, 2008)
The clothing pressure of tight seamless sportswear restricts wearer's movement and causesdiscomfort. In this paper, a research on the dynamic pressure comfort of tight seamless sportswear isconducted. The study samples are four men's sportswear of an ordinary style. They are made of samematerial with same style and cylinder diameter but with different organization structure and knittingmethods. The dynamic pressure and pressure sense of different positions in tight seamless sportswearare tested by young men of similar body sizes. In combination with fuzzy mathematics and box controlgraph, the methods of objective and subjective evaluation are used to describe the pressure of positionsand garments, and to summarize the relationship between pressure and comfort. The study will providesome useful guidance for design and production of tight seamless sportswear.